Monitoring macro voids in mortars by computerized tomography method. (March 2015) - Tekin, Ilker; Birgul, Recep; Ozgur Yaman, Ismail; Gencel, Osman; Yilmaz Aruntas, Huseyin
Highlights: XCT is an effective way to monitor macro voids in mortars. The compaction method of mortars is affected to void distribution. Wide range XCT FOV makes some geometrical mistakes on images. Small changes to the void were not directly affected to compressive strength. Abstract: This study aims to investigate the use of ground pumice powder (PP) in cement production and to monitor void developments in mortars by X-ray Computerized Tomography (CT) which is a nondestructive test method. PP-blended cements were produced by replacing ordinary Portland cement with PP at 0% (control), 5%, 10% and 15% by weight. Paste and mortar specimens were manufactured by these blended cements. Some of the physical and mechanical tests are carried out on these mortar specimens. Experimental results showed that macro void developments in 100-day period for mortars with different PP replacement ratios exhibited different reduction in void ratios.